The Influence of Service Quality on Consumer Satisfaction Levels - Tresna Fatmawati; Henni Febriawati; Achmad Faisal Rizal; Ferry Adhinata; Sarkawi Sarkawi (Institut Citra Internasional, 2026)
Service quality plays a crucial role in shaping customer satisfaction, particularly in healthcare services such as child therapy. This study aims to determine the effect of service quality on customer satisfaction levels at Asri Therapy Center in 2025. This study used a quantitative approach with a cross-sectional design. The number of respondents was 38 parents of children undergoing therapy, selected using a total sampling technique. The research instrument was a questionnaire based on five dimensions of service quality: tangibles, reliability, responsiveness, assurance, and empathy. Data were analyzed descriptively and through a Chi-Square test. The results showed that all respondents (100%) rated the service quality at Asri Therapy Center as good, and all also reported being satisfied with the service received. The Chi-Square test results showed a p-value of 0.031 (<0.05), indicating a significant relationship between service quality and customer satisfaction. It can be concluded that the better the service quality provided, the higher the level of customer satisfaction.